Photo-identification rate and wide-scale movement of common minke whales (Balaenoptera acutorostrata) in the coastal waters of Faxaflói and Skjálfandi Bays, Iceland - Bertulli, C. G.; Rasmussen, M. H.; Tetley, M. J. (J. Cetacean Res. Manage., 2023)
Information on movement and site fidelity is important for conservation and management. Photo-ID of common minke whales (Balaenoptera acutorostrata) was conducted from whalewatching vessels within the coastal waters of Faxaflói (a bay on the southwest coast of Iceland) and Skjálfandi (a bay on the northeast coast) between 2007–10 and 2001–10 respectively, to examine fidelity to the sampling locations and movement between them. Images of 292 individual minke whales were obtained in Faxaflói and 61 in Skjálfandi, with an overall ‘annual re-capture proportion’ of 23.3% in the former and 16.4% in the latter. Most (about 80%) of the resighted animals in each bay were re-sighted in one year only. The total number of identified whales has increased in both Faxaflói and Skjálfandi Bays since 2007 and 2001 respectively, suggesting the existence of an open population in both bays. One match was found between the two bays, eight years apart; the distance was approximately 600km between southwest and northeast Iceland. This study shows the value of photo-ID studies from platforms of opportunity such as whalewatching vessels. More data are required from broader geographic areas before firm conclusions can be drawn about movements and site fidelity within Icelandic waters.